Complementary Honey Therapy To Reduce The Frequency Of Diarrhea In Toddlers: Literature Review - Puspita , Uci Nurhayati; Muhith, Abdul; Zahro, Chilyatiz (Chakra Brahmanda Lentera Institute, 2023)
Background: Diarrhea is a major health problem in children that still occurs frequently and even has the potential to become an outbreak (extraordinary event), which is often accompanied by death due to the release of fluid from the body caused by bacteria and causing dehydration in children. This literature review aims to determine the effect of honey complementary therapy on reducing the frequency of diarrhea in toddlers. Methods: The method used in this article is a literature review using journal databases from Google Scholar, Pubmed, and Science Direct in the 2020-2023 period with the keywords